Introduction : la Nouvelle-France et l’Atlantique - Desbarats, Catherine; Wien, Thomas (Revue d’histoire de l’Amérique française, 2011)
Un article de la revue Revue d’histoire de l’Amérique française, diffusée par la plateforme Érudit.

Les réjouissances populaires en Amérique française et la construction d’identités sociales (1770-1870) - Dumont, Mikael (Université de Montréal, 2020)
This thesis focuses on the social roles of popular celebrations in rural French-speaking communities of North America between 1770 and 1870. It approaches the subject of festivals by looking more precisely at the festivity. The main objective is to highlight how the festivities, which we call popular celebrations, influence the functioning of North American francophone societies. What roles do popular celebrations play in the social life of the inhabitants of these societies? What impacts do they have on individual and collective identities? Do they retain the same characteristics from one society to another or do they adapt to different environments and contexts? How do they develop and evolve over time? What are the elements that influence their evolution? In order to answer these questions, the focus is on studying certain popular celebrations among four rural populations of French origin, namely the inhabitants of the St. Lawrence Valley, the Detroit region, the Illinois Country and Louisiana (more specifically, the inhabitants of Acadian origin). Based on published monographs, personal manuscripts, church correspondence, fictional literature and the work of folklorists, each of the five chapters represents a case study that shows how popular celebrations are influenced by the context in which people live and how festive sociability is involved in the construction of different social identities, such as those relating to race, gender and class. In the first chapter, a look at the weddings of Canadians and Louisianans of Acadian origin in the late 18th and mid-19th centuries reveals that food, drink, music and dance are very much in evidence, but above all that these festivities are the scene of many rites of passage for the new couple, and often more particularly for the wife, allowing the community to control the recognition and formalization of their social and sexual union. In the second and third chapters, the analysis of the guignolée, Epiphany and especially the carnival in Canada, Detroit and the villages of the Illinois Country shows that this festive period is influenced by the winter climate of the northern colonies and that it remains a key moment in the social life of the inhabitants. Among other things, it is synonymous in all three regions with meetings, dinners and balls during which residents determine who has the right to court with whom, that is, young people of the same social rank, and those who are an integral part of their community and those who are excluded from it, that is, poorer residents (St. Lawrence Valley) or Blacks and Indigenous people (Illinois Country). In the fourth chapter, the study of the evolution of the Sunday culture of Louisianans of Acadian origin highlights how, despite the success, over time, of the Catholic Church in its attempts to impose the sanctification of this day, house balls persist, being transferred to Saturdays, and contribute to the construction of this population’s racial identity. In the last chapter, an examination of the evolution of the May Day celebrations shows the effectiveness of reciprocal relationships in reinforcing and strengthening the social hierarchy in rural Canada, that is, between country people and a member of the local elite (seigneur or militia captain). This thesis enriches the existing historiography of festival in French America, which hardly addresses the subject of rural popular celebrations from the perspective of festive sociability. It shows that these celebrations are closely linked to the contextual aspects of each of the four regions studied, i.e. the demography, the presence of other ethnic groups, the climate, the geography, the gender relations, the economy, the political situation and the social hierarchy. Francophone inhabitants of rural areas adapt their popular celebrations to the particularities of their society, but those celebrations still preserve, sometimes until the 1870s, their regulatory functions of reproducing social, economic, gender and racial hierarchies. In other words, they are a tool that allows these Francophones not only to affirm their identity of French origin, but also to clearly identify the people who can or cannot claim this identity and the inequalities that are produced within this process.
Keywords: Amérique française; French America; History - Canadian / Histoire - Canadienne (UMI : 0334); XVIIIe-XIXe siècles; campagne; country people; countryside; eighteenth-nineteenth centuries; festival; fête; identities; identités; inequalities; inégalités; popular celebrations; ruraux; réjouissances populaires; sociability; sociabilité